PENGARUH KONSENTRASI PATI UBI TALAS (Colocasia esculenta) DAN JENIS PLASTICIZER TERHADAP KARAKTERISTIK BIOPLASTIK - Situmorang, Farida Unggul; Hartiati, Amna; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
This study aims to know the effect of the concetration of taro tuber starch and plasticizer type and their interactions on the characteristics of bioplastics, and to determine the concentration of taro tuber starch and plasticizer type which produces bioplastics with the best characteristics. The research used factorial randomized block design. The first factor is the concentration of taro tuber starch consisting of 3 levels 5, 6 and 7% (w/w). The second factor is the plasticizer type consisting of 3 levels that is glycerol, sorbytol and mixture plasticizer glycerol and sorbitol (1:1). Each treatment are grouped into two time-based of making bioplastics so there are 18 experimental units. Variabels observed tensile strength, elongation at break, Young’s modulus, swelling, biodegradation and FTIR. The data obtained were analyzed of variant and test Tukey’s. The result showed that the concentration of taro tuber starch and type of plasticizer had a very significant effect on tensile strength, elongation at break, Young’s Modulus and swelling but the type of plasticizer had no significant effect on biodegradation. Interaction between treatments has a very significant effect on Young’s Modulus and swelling, a significant effect on tensile strength and no significant effect on elongation at break and biodegradation. The concentration of starch 6% with plasticizer glycerol produces the best characteristics of bioplastics with tensile strength 2.270 0.057 MPa, elongation at break 14.5 0.01 %, Young’s modulus 15.683 1.155 MPa, swelling 29.88 1.02 % and biodegradability 6-7 days. FTIR analysis proved the existence of hydroxyl (O-H), carbonyl (C=O), C=C aromatic, carboxyl (C-O), C-H aromatic, and hydrocarbons –(CH 2 )n in the bioplastic. Keywords: Bioplastics, concentration of taro tuber starch, glycerol, sorbytol